2004
DOI: 10.1002/pen.20235
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic deformation behavior of an epoxy polymer. Part II: Predictions of viscoelastic constitutive models

Abstract: The experimental results presented in Part I of this study were used to evaluate the predictive capabilities of two viscoelastic constitutive models. One of the models, developed by Xia and Ellyin, is in a differential form. The other, which is a modified Schapery model by Lai and Bakker, is in an integral form. The results of the comparison indicate that the Xia‐Ellyin constitutive model simulated the experimental observations well. This was attributed to the existence of a general rule that delineates the lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
42
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(43 citation statements)
references
References 17 publications
0
42
1
Order By: Relevance
“…As only a weakly viscoelastic effect is considered and the underlying kinematic hardening part is not high enough to induce the plastic deformation during unloading phase, the current model cannot predict correctly this unloading behavior. In the literature, the nonlinearity upon unloading of glassy polymers can be modeled by considering a nonlinear viscoeslastic behavior as demonstrated by Xia et al (2005Xia et al ( , 2006; Colak (2005); Anand and Ames (2006). The constitutive models considering the kinematic hardening can account for this nonlinear response at large strains Ames et al, 2009), however they do not adequately account for this effect at small strains (Anand and Ames, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…As only a weakly viscoelastic effect is considered and the underlying kinematic hardening part is not high enough to induce the plastic deformation during unloading phase, the current model cannot predict correctly this unloading behavior. In the literature, the nonlinearity upon unloading of glassy polymers can be modeled by considering a nonlinear viscoeslastic behavior as demonstrated by Xia et al (2005Xia et al ( , 2006; Colak (2005); Anand and Ames (2006). The constitutive models considering the kinematic hardening can account for this nonlinear response at large strains Ames et al, 2009), however they do not adequately account for this effect at small strains (Anand and Ames, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…Only using the static tension-elongation curve was not sufficient, and a true "time domain" rheological model still required further effort. In fact, the viscoelasticity and viscoplasticity also exist in other materials such as the HighDensity Polyethylene (HDPE) (Lai and Bakker, 1995;Haj-Ali and Muliana, 2004;Kim and Muliana, 2009), the epoxy resin (Xia et al, 2005), and the asphalt (Ye et al, 2010). The research achievements of the constitutive model for these materials could give reference to the present work.…”
Section: Introductionmentioning
confidence: 92%
“…The data were used to evaluate the performance of two nonlinear viscoelastic constitutive models (Xia et al, 2005b), where a general loading/unloading criterion and a 'switch rule' was proposed. It was clearly shown that the introduction of such a rule is essential in properly simulating the cyclic deformation behavior of the epoxy polymer.…”
Section: Hysteresis Effect In Cyclic Loadingmentioning
confidence: 99%